Pulse Doppler radar principles, technology, applications - Alabaster, Clive (Raleigh, NC SciTech Publishing, 2012)
The book is organized into three parts, each one building on the material of the previous sections. Part I (Chapters 1-8) covers the basic principles to lay sound foundations for the following parts of the book. It emphasizes classic processing techniques, especially the fast Fourier transform (FFT), and microwave engineering issues, antennas, and hardware. The second part of the book deals with the theory and techniques specific to pulse Doppler radar. This is subdivided into Part IIA (Chapters 9-10), which covers high PRF pulse Doppler, and Part IIB (Chapters 11-15), which covers medium PRF pulse Doppler. A major theme is that of PRF selection and optimization, other waveform design issues, and the problem of ghosting. While high and medium PRF pulse Doppler techniques have become synonymous with airborne fire control radars, they are used over a broad spectrum of airborne and surface-based radar applications. Part II does emphasize the airborne radar case, but it does not neglect the surface-based radar. Finally, Part III (Chapters 16-19) presents a series of four case studies. Each of these case studies applies the material of Part II whilst also highlighting additional radar techniques (and, in some cases, non-radar considerations) specific to the application. Such is the prevalence of pulse Doppler radars today; the number of case studies that could have been considered is well into double figures. However, the four presented here suffice to illustrate the wide variety of pulse Doppler radar applications.
Electronic reproduction.
Keywords: Doppler radar; Pulse techniques (Electronics); Airplanes -- Radar equipment; Antennas (Electronics).; Fourier transformations; Radar in aeronautics; Electronic books